Mediator effects of customers’ attitude on factors influencing intention to purchase organic beverages in Vietnam - Truong, Dinh Duc; Huong, Tran Thi Lan (Frontiers in Sustainable Food Systems, 2025)
With rapid economic growth, Vietnamese people are increasingly interested in consuming organic food to protect the health of themselves, their families, and the living environment. This study investigates the direct and mediating effects of determinants studying Vietnamese consumers’ intention toward purchasing organic beverages. We apply the theory of planned behavior and attitude–behavior–context model to establish experimental models and research hypotheses. The study collected primary data through a survey of 550 customers in six urban districts in Hanoi. Data are analyzed using AMOS software with descriptive statistics, Cronbach’s alpha test, confirmatory factor analysis, and structural equation modeling. The results show that there is a significant positive relationship between customers’ attitudes and intention to buy organic drinks. Five independent factors directly affect the attitude and intention to consume organic beverages, including environmental concern, health awareness, price perception, subjective norms, and marketing and communication. Furthermore, there are full mediating effects of attitudes on the relations between the five above factors and organic beverage buying intention. The study proposes some management implications including increasing customers about perception of organic beverages through social network communication, promoting social inclusion in building images of organic food, designing proper price systems for customers, and involving them in the process of building social norms about organic beverage consumption.